Takhrij al-Furu‘ ‘ala al-Usul dan sumbangannya dalam menyelesaikan isu-isu muamalat semasa: Analisis kaedah-kaedah terpilih dalam kitab Takhrij al-Furu‘ ‘ala al-Usul oleh al-Zanjani / Ahmad Zakirullah Mohamed Shaarni - Ahmad Zakirullah, Mohamed Shaarni (2017)
Takhrīj al-Furū’ ʻalā al-Uṣūl is an application of methods of deducing the hukm/istinbāṭ used in a madhhab to solve Shariah issues. Through this application, evidences and arguments used by the ulama and fuqaha`s madhhab in issuing the ijtihād based on their understanding of the arguments can be comprehended. Through these ijtihād by the Mukharrij/person who performs the takhrīj process, the madhhab continues to survive and evolve through time even after the passing of the founders of the madhhab. One of the prominent figures who contributed to the development of this field of study is Imam Mahmūd bin Aḥmad al-Zanjānī al-Shāfi‘ī through his magnum opus titled Takhrīj al-Furū’ ʻalā al-Uṣūl. This classical book is highly valued and serves as a means of continuity of the Uṣūl al-Fiqh and fiqh of Shāfiʻī`s madhhab. Thus, the purpose of this study is to analyse the importance of Takhrīj al-Furū’ ‘alā al- Uṣūl in deducing Shariah laws. In analyzing its importance, selected methods from the book are analyzed and applied in deriving the solutions to Muamalat issues in Malaysia. This study is prepared entirely using the library method. Selected methods of uṣūl and fiqh from the book are analyzed based on the Mutakallimin`s writing method, and the comparison also be made against the fuqaha method. The study found that methods of uṣūl and fiqh derived from the Takhrīj al-Furū‘ ʻalā al-Uṣūl by al-Zanjānī could solve various contemporary furū’/issues related to Muamalat and Islamic finance particularly on Islamic banking, Takaful, Islamic capital market, zakat, wakaf, etc. Some of the contemporary issues as revealed and discussed by the study are the obligation of zakat on Company Limited by Guarantee although it has no owner, zakat on debt-based ṣukūk even before maturity of the instrument; as well as zakat on pooled-asset, i.e. khulṭah. Another finding of the study is the prohibition of Bay’ al-Wafā’ contract as it is similar to loan (qard) of which interest is charged, as well as other examples of contemporary issues which have been discussed in this study.